METHODS AND WAYS TO EXPLAIN POLYSEMANTIC TERMS IN " EXPLANATORY DICTIONARY OF THE UZBEK LANGUAGE " (Conferencea, 2023)
This dissertation examines the issues of choice, interpretation of terms in the "Explanatory dictionary of the Uzbek language", in particular, the reflection of a polysemous term in the dictionary. In our explanatory dictionary, which is considered the main basic dictionary, and can observe some differences between how terms are given and interpreted in general, and however a word interpreted in terminology.